Autopercepción de la eficacia en enfermeras neonatales entrenadas en una simulación in situ de reanimación cardio pulmonar neonatal - Samanez-Obeso, Angel Francisco (2022)
Introduction. The care of the neonate in critical condition is a complex situation that requires of training and continuing education, through the incorporation of active methodologies of learning, as the clinical simulation. Objective: To describe the self-perception of efficacy of the in-situ clinical simulation. Methods: Descriptive, observational and cross-sectional study. The sample was intentional and included participants of the clinical stage of Reanimation Cardiopulmonary in the Unit of Neonatal Intermediate Cares of the Instituto Nacional de Salud del Niño San Borja, Lima – Peru. The unit of analysis was the nurses with specialty in neonatology. We applied the Tool of Efficiency of Simulation - Modified. Results. 12 nurses participated, more than 80% of them considered that the in-situ clinical simulation increases their confidence and develops a favorable learning environment in technical and non-technical skills. Conclusions. The in-situ clinical simulation generated a high percentage of satisfaction as a methodology of learning.